Characterization of brusatol self-microemulsifying drug delivery system and its therapeutic effect against dextran sodium sulfate-induced ulcerative colitis in mice. (1st January 2017) - Zhou, Jiangtao; Tan, Lihua; Xie, Jianhui; Lai, Zhengquan; Huang, Yanfeng; Qu, Chang; Luo, Dandan; Lin, Zhixiu; Huang, Ping; Su, Ziren; Xie, Youliang
Abstract: Brusatol (BR) is one of the main bioactive components derived from Brucea javanica, a medicinal herb historically used in the treatment of dysenteric disorders (also known as ulcerative colitis(UC)). Due to its poor aqueous solubility, a novel brusatol self-microemulsifying drug delivery system (BR-SMEDDS) nanoformulation with smaller size, higher negative zeta potential and drug content, and excellent stability was developed. The appearance of BR-SMEDDS remained clear and transparent, and transmission electron microscopy showed microemulsion droplets to be spherical with homogeneous distribution. Pharmacokinetic parameters indicated that oral bioavailability was greatly improved by BR-SMEDDS as compared with aqueous suspension. Meanwhile, the anti-colitis activity of BR-SMEDDS was evaluated on dextran sodium sulfate (DSS)-induced colitis mice model. The result illustrated that the nano-formation significantly reduced the body weight loss, recovered colon length, decreased disease activity index and microscopic score, regulated immune-inflammatory cytokines, diminished oxidative stress and repressed the colonic expression of myeloid differentiation factor 88 (MyD88), toll-like receptor 4 (TLR4) and nuclear factor kappa B p65 (NF-κB p65) proteins. Our findings demonstrated for the first time that BR could effectively attenuate colonic inflammation in mice, at least partially, via favorable regulation of anti-oxidative and anti-inflammatory status and inhibition of the TLR4-linked NF-κB signaling pathway. The BR nano-formulation was superior to BR suspension and sulphasalazine, in treating experimental UC, and exhibited similar effect with azathioprine, with much smaller dosage. The enhanced anti-UC effect of BR might be intimately associated with the improved pharmacokinetic property by SMEDDS. The developed nano-delivery system might thus be a promising candidate for colitis treatment.